Pengaruh Kualitas Pelayanan Dan Citra Yayasan Terhadap Kepuasan Siswa Di Yayasan Pendidikan Islam At-Tadzkir Nur Ghazali - Anisa Fathi Arsi; Ety Nurhayaty (Ikatan Dosen Menulis, 2024)
At-Tadzkir Nur Ghazali Islamic Education Foundation is an Islamic education provider institution whose legality is registered in MENKUMHAM No. AHU-0016685.AH.01.04. In 2020, the organization of education under its care includes TPQ, PAUDQU, MDTA, Ponpes At-Tadzkir Nur Ghazali, and junior high schools and vocational schools. The purpose of this study was to determine the effect of service quality and foundation image on student satisfaction. This study uses quantitative descriptive methods with data collection techniques in the form of observation and questionnaires. The population used was 63 students and in withdrawing the sample using a total sample. Furthermore, the data were tested for validity and reliability and carried out normality tests, heteroscedasticity tests, multicollinearity tests. Data analysis was carried out using multiple linear regression equation tests with the results Y = -3.140 + 0.040 + 0.764 which shows that service quality and foundation image simultaneously affect student satisfaction. however, partially service quality has no effect on student satisfaction and foundation image affects student satisfaction.